Tillage Study for Corn and Soybean: Comparing Vertical, Deep, and No-Tillage - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2017)
A tillage study comparing no-tillage, shallow tillage, and deep tillage in alternate or every year for corn and soybeans in annual rotation was conducted at Kansas River Valley Experiment Field for five years. The influence of tillage system on corn yield appears to be increasing with time, soybean yields appear to perform equally well with any of the systems. As the study progresses, the corn yields were increased with deep tillage occurring sometime in the cropping rotation.
Keywords: Tillage; corn; soybean; vertical till; no-tillage